Outcome of Uretero Renoscopic Lithotripsy (URSL) with Holmium LASER Vs Pneumatic Lithotripter for Lower Ureteric Stones, Experience from University Hospital of Nepal - Joshi, H.N.; Singh, A.K.; Koirala, N.; Karmacharya, R.M. (Kathmandu University Medical Journal, 2020)
Background There are various methods of endoluminal ureteral stone fragmentation. Among various modalities Laser lithotripsy and Pneumatic lithotripsy are commonly used and have shown comparable outcomes. Objective To compare the efficacy and outcome of laser and pneumatic lithotripsy in a patient with lower ureteric calculi. The comparison will be done in stone free rate, migration of stone and complication of the procedure. Method This is a prospective comparative study in a cohort of patients at University Hospital with Lower Ureteric stone. Ninety patients were randomized in to two groups (Laser Lithotripsy Vs Pneumatic Lithotripsy) during the study period. The purpose of this study was to measure the immediate stone free rate, intra-operative complications, mean operative time, post-operative complication and if any stone retention after six weeks follow up. Result Both the groups were similar in Age and Gender. Immediate stone free rate was slightly higher in Laser lithotripsy group (97.77%) in comparison to Pneumatic lithotripter group (84.44%) with p=0.507 which is not statistically significant. There was statistical difference in terms of stone migration rate, mean operation time in favor of Laser Lithotripsy group (p<0.01, in both parameters). There were no immediate complications in both the group however there were three cases of short segment ureteric strictures (6.66%) in case of Pneumatic lithotripsy on six weeks follow up which was managed conservatively. Conclusion Both LASER lithotripter and Pneumatic lithotripter are equally efficacious modality of endoluminal URSL in lower ureteric stone with similar Stone Free Rate. Laser lithotripsy showed lower frequency of stone migration and had shorter procedure time.